Sistem Monitoring Produksi Berbasis Web Dengan Sistem Peringatan Untuk Mendukung Produktivitas Dan Pengawasan Produksi Di PT. Menara Kudus Indonesia - Aderochman, Itsnain Nur; Irawan, Yudie; Muzid, Syafiul (STIKOM Tunas Bangsa Pematangsiantar, 2025)
PT Menara Kudus Indonesia is a printing company with a long production flow, starting from ordering, prepress, production, to delivery. All processes are interconnected, but data recording is still carried out manually using spreadsheets, making it difficult for management to monitor the overall production status. This condition causes communication barriers between divisions, delays in information delivery, and production mismatches. Monitoring processes should assist management and related divisions in tracking order status and providing notifications for problems, but they are not yet optimal due to the absence of an integrated system. Therefore, this study aims to develop a web-based production monitoring system using the Rapid Application Development (RAD) method to support supervision, accelerate communication, and improve productivity. The RAD methodology was chosen because it involves users actively through iterative stages, ensuring the system meets company needs. The results show that the designed system can display real-time production status, provide automatic alerts when issues occur, and support management in decision-making. With this system, PT Menara Kudus Indonesia can optimize production monitoring, improve timeliness, and minimize workflow disruptions